2011
DOI: 10.1007/s11255-010-9893-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of secondary ureteral implantation after kidney transplantation

Abstract: Secondary ureteral implantation can be performed with acceptable morbidity and good long-term transplant outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Widespread use of routine ureteral stenting during renal allograft transplantation (1,2), improved procurement methods, and lower perioperative steroid regimens (3) have decreased but not eliminated the overall incidence of ureteral complications. There are many large retrospective consecutive series (n = 789-2000) that have looked at the incidence of ureteral complications in the setting of renal allotransplantation (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The overall reported incidence ranges from 4.8 to 9.2% in these select studies; the stenosis rate ranges from 2.4 to 6.5%, and the urine leak rate ranges from 1.8 to 5.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread use of routine ureteral stenting during renal allograft transplantation (1,2), improved procurement methods, and lower perioperative steroid regimens (3) have decreased but not eliminated the overall incidence of ureteral complications. There are many large retrospective consecutive series (n = 789-2000) that have looked at the incidence of ureteral complications in the setting of renal allotransplantation (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The overall reported incidence ranges from 4.8 to 9.2% in these select studies; the stenosis rate ranges from 2.4 to 6.5%, and the urine leak rate ranges from 1.8 to 5.4%.…”
Section: Introductionmentioning
confidence: 99%
“…George et al reported PUJ complications occurred after about 6 years from kidney transplant [4]. While Doehn et al reported ureteral complications occurred after 2129 days [5]. These periods were far more than the follow-up time reported by Tisljar et al [1].…”
Section: Editorsmentioning
confidence: 96%
“…The main treatments for these complications are intracavitary therapy and open surgery, with the main goals being the reconstruction of the transplanted kidney's urinary tract, which thus frees the patient from undergoing a renal graft ostomy and the insertion of a long-term indwelling double J stent. The open surgery failure rate has been reported to be 7% to 8% (3,4), with multiple reasons for these failures evidenced, for example, inadequate preoperative preparation (5). This article aims to summarize the author's clinical experiences related to selecting the most appropriate preoperative surgical plan for a successful surgery.…”
Section: Introductionmentioning
confidence: 99%